Dynamic driver of digital devices for embedded systems design - Kunle Akinde, Olusola; Adeola Ajagbe, Sunday; Abiodun Afe, Rotimi; Bethel Mutanga, Murimo (Institute of Advanced Engineering and Science, 2025)
A wide-ranging exploration of the diverse applications of embedded systems (ES) is delved in in this study, tracing their evolution from early industrial control to their current pervasive influence on modern technological landscapes. The study underscores their crucial role in various sectors, including consumer electronics, automotive technology, medical and healthcare, education and research, industrial automation, telecommunications, smart cities, edge computing, and the convergence of 5G and artificial intelligence (AI). It accentuates the versatility and transformative potential of ES. The paper reviews the historical, current, and future contributions and evolution of ES in shaping contemporary technological landscapes. Emphasizing the broad impact of ES, the paper highlights their significance for researchers, practitioners, and enthusiasts navigating the dynamic intersection of technology and diverse disciplines.